Impact of E-Filing of Tax Returns on Tax Revenue - DR. SP. Mathiraj, M. Thivya bharathi (International Journal of Advanced Science and Technology, 2020)
The E-filing is the very important of the income tax payers. It will be used to income taxpayer’s use to easy file the tax amount to pay income tax department. The E-filing hasintroduced 1986 but the compulsory filing of tax through online E-filing announcement ofincome tax department 2013. This paper deals with the impact of e-filing of returns on taxrevenue. This paper study with before and after compulsory filing of online payment of e-filingof tax revenue and number of Tax Payers to return the income tax and the impact of tax amount will be tax revenue collected the various sectors. Keyword:. E-filing, Tax Revenue, Tax Returns